SOME FEATURES of the DISTRIBUTION, OCCURRENCE and behavior of ROE DEER (Capreolus capreolus l. 1758., Cervidae) in the MOUNTAINOUS PART of the REPUBLIC of CHECHNYA - Hussein Junuzovic Andrianov; Aslanbek Magomedovich Bakiev; Fatima Tuganovna Tоchieva (Юг России: экология, развитие, 2015)
The subject of this article is the study of certain characteristics of the distribution and abundance of the Caucasus subspecies of European roe deer in the Chechen Republic. The purpose of this study is to analyze the most characteristic features of the species biology and ecology, Adaptive conduct. Methods. Direct observation methods used, the collection traces activity and accounting numbers. The results. The article presents the results of long-term observations of Roe in the Chechen Republic in different seasons of the year. Data on the distribution and characteristics of the region, the distribution of habitats. Discusses the results of reproduction and food species, seasonal cikle of life and some features of behaviour in terms of the Republic. Field of application. The research results can be used to develop measures for the preservation and restoration of the main hunting-fishing species of the Chechen Republic, in carrying out biotechnical activities on hunting farms.